DINAMIKA INTERAKSI SOSIAL PADA PAGUYUBAN PASUNDAN DI KOTA TERNATE - Enang Yusuf Nurjaman (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
Sundanese as the second largest ethnic group after Java, known as a tribe who does not like to migrate, comfortable natural conditions and the stigma of